2020
DOI: 10.3390/children7060050
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Microbiome in Food Allergy: A Review

Abstract: Food allergies are common and estimated to affect 8% of children and 11% of adults in the United States. They pose a significant burden—physical, economic and social—to those affected. There is currently no available cure for food allergies. Emerging evidence suggests that the microbiome contributes to the development and manifestations of atopic disease. According to the hygiene hypothesis, children growing up with older siblings have a lower incidence of allergic disease compared with children from smaller f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 95 publications
1
46
0
1
Order By: Relevance
“…A breakdown in tolerance can lead to adverse immune responses targeting food antigens. Dietary fibre and probiotic SCFA‐producing bacteria are proposed as therapeutic strategies for food allergy due to their ability to alter microbiome composition, promote immune tolerance and improve mucosal health and barrier function as reviewed recently 105‐107 …”
Section: Macronutrients: Impact On Microbiome and Mucous Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…A breakdown in tolerance can lead to adverse immune responses targeting food antigens. Dietary fibre and probiotic SCFA‐producing bacteria are proposed as therapeutic strategies for food allergy due to their ability to alter microbiome composition, promote immune tolerance and improve mucosal health and barrier function as reviewed recently 105‐107 …”
Section: Macronutrients: Impact On Microbiome and Mucous Barriermentioning
confidence: 99%
“…Dietary fibre and probiotic SCFA-producing bacteria are proposed as therapeutic strategies for food allergy due to their ability to alter microbiome composition, promote immune tolerance and improve mucosal health and barrier function as reviewed recently. [105][106][107] In human studies, the impact of fibre on GI barrier function depends on numerous factors, including the study population, GIT location and the type of fibre administered. A recent systematic review did not identify any studies demonstrating that lower fibre intake was a risk factor for intestinal permeability.…”
Section: F I G U R Ementioning
confidence: 99%
“…Supplementation of prebiotics as food ingredients has been proposed to prevent several inflammatory diseases [23][24][25][26][27] as well as allergies [10,28,29,30,31,32]. Cohort studies have indicated that one of the factors preceding the development of food allergies is gut dysbiosis [2,33,34]. Therefore, gut microbiota have gained attention as a target of intervention against allergies, especially with prebiotics.…”
Section: Introductionmentioning
confidence: 99%
“…At present, in the treatment and prevention of food allergies, bacterial therapy has attracted more and more attention from scholars. They believe that one of the effective ways to prevent allergic diseases is fecal flora transplantation ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%